2013
DOI: 10.5704/moj.1303.012
|View full text |Cite
|
Sign up to set email alerts
|

The NRAMP1 polymorphism as a risk factor for tuberculous spondylitis

Abstract: In the present study, we analysed the association between the incidence of tuberculous spondylitis with the Natural Resistance Associated Macrophage Protein 1 (NRAMP1, also known as Solute Carrier Family 11a member1) polymorphism by studying the genetic segregation of this polymorphism and the incidence of the disease among members of the West Javanese population undergoing surgery for tuberculous spondylitis at our institution. We compared the distribution of NRAMP1 polymorphism at two specific sites, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In endemic regions, such as Indonesia, the incidence of spinal tuberculosis is affected by several genetic factors that caused increased susceptibility to the disease, such as NRAMP1 gene polymorphism. 2 Studies involving West Javanese subjects had found increased susceptibility towards spinal tuberculosis due to Fok1 vitamin D receptor gene polymorphisms and vitamin D deficiency. 3 Patients with TB spondylitis and neurological deficits may have better outcome if surgery treatment was carried out in the early course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In endemic regions, such as Indonesia, the incidence of spinal tuberculosis is affected by several genetic factors that caused increased susceptibility to the disease, such as NRAMP1 gene polymorphism. 2 Studies involving West Javanese subjects had found increased susceptibility towards spinal tuberculosis due to Fok1 vitamin D receptor gene polymorphisms and vitamin D deficiency. 3 Patients with TB spondylitis and neurological deficits may have better outcome if surgery treatment was carried out in the early course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Disease susceptibility is determined by a variety of factors, not just following the Mendelian genetic model. Multiple genes lead to STB genetic susceptibility, such as NRAMP1, the vitamin D receptor (VDR) [ 5 8 ]. Two methods are used to detect genetic susceptibility: candidate gene strategy and whole-genome scanning strategy.…”
Section: Introductionmentioning
confidence: 99%